(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Spatial memory is one of the necessary components of our typical day-to-day life. Therefore, its impairment should be alleviated or prevented. The purpose of this study was to assess the effects of swimming exercise on spatial memory performance and hippocampal oxidative stress in male Long-Evans rats with colchicine-induced memory impairment. Methods: Thirty male aged 8 standard deviation (2) weeks; weight 225 (75) gm Long-Evans rats were assigned to normal control, sham control, colchicine control, pre colchicine swimming exercise and post colchicine swimming exercise groups. A memory-impaired rat model was established by administering colchicine intrahippocampally. Swimming exercise was performed before and after spatial memory impairment. For spatial reference and working memory performance evaluation, the Morris water maze test was used. Hippocampal malondialdehyde and glutathione peroxidase were estimated for oxidative stress assessment in all rats. Results: Intrahippocampal colchicine administration significantly impaired spatial memory, and elevated malondialdehyde, decreased glutathione peroxidase level in the hippocampus of colchicine control rats. In contrast, both pre- and post-treatment with swimming exercise significantly improved learning and spatial memory retention and attenuated oxidative damage to nearly normal levels. Conclusion: Swimming exercise prevents as well as alleviates colchicine-induced spatial memory impairment along with hippocampal oxidative stress in male Long-Evans rats. Moreover, this swimming exercise schedule is sufficient to reverse these alarming consequences to almost normal.